2024
DOI: 10.7759/cureus.54907
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in Interventional Radiology: Transforming Training Paradigms

James Baker,
Antony Antypas,
Prashant Aggarwal
et al.

Abstract: The ascent of medical technology places augmented reality (AR) at the forefront of potential advancements in interventional radiology (IR) training. This review delves into the symbiotic relationship between AR and conventional IR training, casting light on the opportunities and hurdles intrinsic to this integration. A targeted literature review was conducted using the databases PubMed, Cochrane Library, and Embase. Search terms included (((“Augmented Reality” OR “Virtual Reality”)) AND ((Education OR Training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…AR holds promise as a transformative technology, particularly in the field of diagnostic imaging, offering clinicians powerful tools to improve patient care and outcomes [18][19][20][21][22].…”
Section: Augmented Reality Integration Into Diagnostic Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…AR holds promise as a transformative technology, particularly in the field of diagnostic imaging, offering clinicians powerful tools to improve patient care and outcomes [18][19][20][21][22].…”
Section: Augmented Reality Integration Into Diagnostic Imagingmentioning
confidence: 99%
“…In the realm of interventional radiology (IR) training, where imaging is also crucial, the synergistic relationship between AR and conventional training methodologies has been a subject of increasing interest [21]. Despite challenges such as small sample sizes and technological constraints, studies have demonstrated the potential of AR to improve procedural accuracy, reduce training duration, and boost trainee confidence [21].…”
Section: Augmented Reality Integration Into Diagnostic Imagingmentioning
confidence: 99%
See 1 more Smart Citation